2019
DOI: 10.3390/en12203835
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Wind and Wave Energy Assessment in the North Indian Ocean

Abstract: With increasing energy shortages and global warming, clean and renewable energy sources, such as wind and wave energy, have gained widespread attention. In this study, the third-generation wave model WAVEWATCH-III (WW3) is used to simulate wave height in the North Indian Ocean (NIO), from 2008 to 2017, using the wind data from the European Centre for Medium-Range Weather Forecasts Renalysis datasets. The simulated results show good correlation with data obtained from altimetry. Analysis of wind and wave energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The Indian Ocean, significantly influenced by the monsoon, presents a sea area with high research and application value for analyzing wind energy resource potential. Previous studies have indicated that from 1979 to 2015, the northern Indian Ocean was rich in WERs across most of its area, showing significant growth trends or stability [18]. Research on the shelf seas off the south coast of India has revealed abundant WERs, with particularly high potential for wind power generation during the summer months [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The Indian Ocean, significantly influenced by the monsoon, presents a sea area with high research and application value for analyzing wind energy resource potential. Previous studies have indicated that from 1979 to 2015, the northern Indian Ocean was rich in WERs across most of its area, showing significant growth trends or stability [18]. Research on the shelf seas off the south coast of India has revealed abundant WERs, with particularly high potential for wind power generation during the summer months [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively fewer studies on the Indian Ocean. In recent years, some scholars have only analyzed the spatial distribution of WEI to SWs [41,50,51]. Pourali et al calculated the wave energy at different locations in the northern part of the Gulf of Oman and found that the relative enhancement of wave energy was greater in the western part [41].…”
Section: Introductionmentioning
confidence: 99%
“…Hammar et al found that the southern part of the Western Indian Ocean has a high wave energy potential, with the highest wave energy in southern Madagascar [50]. Yang et al analyzed NIO's wind and wave energy resources based on WW3 (a third-generation ocean wave model), and the results showed that the Somali waters, the Arabian Sea, and the southern NIO have the most abundant wind and wave energy resources, followed by the La Cardiff Sea, while the middle of the NIO is relatively poor [51]. However, there are no studies that have used CMIP6 simulations to predict the WEI to the SWs in the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, researchers from several countries have evaluated the wave power potential of their respective countries or regions (Gonçalves et al 2020;Lo Re et al 2019;Sun et al 2021). For achieving so, they have used the results of the sea states' simulation through third generation wave spectral models, either simulated by themselves (Dong et al 2020;Ribal et al 2020;Yang et al 2019) or obtained from open access databases. In this work, a preliminary assessment of the potentialities of wave power in the seas adjacent to Cuba was carried out in order to envision its future exploitation, using the results of the sea states' simulation every three hours, with the WAVEWATCH III model, available in the databases of the U.S. National Oceanic and Atmospheric Administration (NOAA).…”
Section: Introductionmentioning
confidence: 99%